Development and validation of clinical prediction models for cardiorespiratory fitness in atrial fibrillation patients following radiofrequency catheter ablation - Zhao, Guiling; Sun, Jian; Che, Qianji; Xu, Wenqing; Song, Mengmeng; El-Ansary, Doa; Adams, Roger; Han, Jia; Meng, Shu; Li, Yigang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAssessment of cardiorespiratory fitness (CRF) is imperative in patients with atrial fibrillation (AF) who have had radiofrequency catheter ablation (RFCA). This study aimed to develop and validate CRF prediction models in this population.Methods141 AF patients with RFCA were recruited. The cardiopulmonary exercise test was used to assess CRF with VO2peak and METsmax. Multidimensional predictors (demographics, serum biomarkers, cardiovascular parameters, and motor function parameters) were analyzed through Spearman correlation analysis and stepwise multivariate linear regression analysis. The internal validity of the prediction equation was tested by paired Student's t-test, Pearson correlation analysis and Bland-Altman analysis.ResultsSex, BMI, ln NT-proBNP, glucose (GLU), 6-minute walking distance (6MWD), and systolic blood pressure (SBP) were found to be significantly associated with CRF in this population. Multivariate linear regression generated the equations: VO2peak = 35.080 − 0.286 * BMI − 1.927 * Sex − 1.090 * ln NT-proBNP + 0.011 * 6MWD − 0.039 * SBP − 0.512 * GLU, and METsmax = 9.646 − 0.447 * Sex − 0.260 * ln NT-proBNP − 0.140 * GLU − 0.078 * BMI − 0.016 * SBP + 0.004 * 6MWD, (VO2peak: adjusted R2 = 0.506, and METsmax: adjusted R2 = 0.469, both P < 0.01). Pearson correlations between the predicted values and the measured values showed good validity (VO2peak: r = 0.616, and METsmax: r = 0.581, both P < 0.01). The Bland-Altman analysis showed that the predicted VO2peak values were slightly lower than the measured values (mean difference = −0.13; 95% limits of agreement: −5.20 to 4.93), while the predicted METsmax values were in close agreement with the measured values (mean difference = −0.00; 95% limits of agreement: −1.59 to 1.59).ConclusionSex, BMI, NT-proBNP, glucose, 6MWD, and SBP are robust predictors of VO2peak and METsmax in AF population after RFCA. This study generates and internal validates the first multivariable CRF prediction models with easy-to use clinical paraments in AF patients after RFCA, thereby providing safe and effective alternatives to conventional CPX, which may help to optimize personalized patient management.